The necessity of others: Entrepreneurial self-efficacy, TMT collective efficacy, CEO-TMT interface, and entrepreneurial orientation - Peng, Xiaobao; Song, Xiaofan; Horsey, Emmanuel Mensah (Frontiers in Psychology, 2023)
Entrepreneurial orientation is the key factor for enterprises to obtain competitive advantages in dynamic circumstances. Thus, prior studies established the effect of psychological factors, for instance, entrepreneurial self-efficacy on entrepreneurial orientation using social cognitive theory. However, prior studies presented two main opposite views consisting of a positive and negative relationship between entrepreneurial self-efficacy and entrepreneurial orientation as well as providing no alleyway to enrich this relationship. We join the conversation on the positive linkage and argue on the essence of exploring the black box mechanisms to strengthen enterprises’ entrepreneurial orientation. We employed the social cognitive theory and collected 220 valid responses from CEOs and TMTs from 10 enterprises in the high-tech industrial development zones of nine provinces in China to clarify the effect of top management team (TMT) collective efficacy, and CEO–TMT interface on the link between entrepreneurial self-efficacy and entrepreneurial orientation. Our findings show that entrepreneurial self-efficacy positively affects entrepreneurial orientation. In addition, we found that a higher level of TMT collective efficacy strengthens the positive relationship between entrepreneurial self-efficacy and entrepreneurial orientation. Moreover, we discovered differential moderating effects. First, CEO-TMT interface positively affects entrepreneurial orientation when it interacts with TMT collective efficacy and entrepreneurial self-efficacy. Second, CEO-TMT interface has a significant negative indirect effect on entrepreneurial orientation, when it only interacts with TMT collective efficacy. Our study enriches the entrepreneurial orientation literature by positioning TMT collective efficacy and CEO-TMT interface as social cognitive mechanisms underlying the development of entrepreneurial self-efficacy and entrepreneurial orientation nexus. Thus, we open a window of opportunities for CEOs and decision-makers to maintain a sustainable position in the market, grasping more opportunities in uncertain conditions via timely entries into new markets and maintaining pre-existing ones.